A study on the fine-scale distribution of the tree of heaven (Ailanthus altissima (Mill) Swingle) based on archive and actual data in the Peszér-forest - Erdélyi, Arnold; Hartdégen, Judit; Molnár, Ábel Péter; Hajagos, Gabriella; Vadász, Csaba (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
The success of actions taken against the Tree of Heaven (Ailanthus altissima) at a certain site can be significantly influenced by the knowledge on its fine-scale population dynamics. In our study, we aimed to investigate the spreading history of this tree species in a 1003-ha forest block of Peszér-forest, Central-Hungary. Additionally, a detailed field investigation was carried out by the authors applying full-cover mapping. Regarding this site, the first archive data on the Tree of Heaven originates from 1971. We hypothesize, that the species appeared in this site not much before that year. In the distribution patterns between all the investigated periods a great increase can always be identified. Based on the forest inventory data of 2016, this species was present in nearly 50% of the forest subcompartments, whilst due to our field investigation the value goes up to 90%. In the previous case it is listed among the main tree species in less than 10% of the subcompartments. According to our collected data 25% of the subcompartments are severely infected.